BIOAVAILABLE GRAIN IRON DECLINES FROM OLD TO CURRENT PAKISTANI BREAD WHEAT CULTIVARS - A.Younas; H. A. Sadaqat; M. Farooq; M. Kashif; N. Ahmed (Journal of Animal and Plant Sciences, 2020)
Green revolution is a revolutionary landmark in history of mankind where high yielding wheat varieties were developed to tackle massive famines. However, the genetic base has become narrow in cultivated varieties with improved yields and less bioavailability of micronutrients. An experiment was conducted to check the change in yield production and micronutrients during previous breeding efforts. Land races (44), approved varieties (68) and advanced lines (32) were grown in field in triple test lattice design in experimental area of University of Agriculture Faisalabad during 2016. Statistical analyses revealed a significant difference in yield contributing traits and grain iron. Land races had broader range of all the traits compared to other two groups. Grain iron contents showed higher values in landraces, while grain yield were higher in varieties and advance lines. Correlation and path coefficient analysis revealed change in the relationship of traits and effects of yield contributors in all three groups. Some genotypes were selected and crossed. These selected genotypes and F1 were grown in the same field following year in randomized complete block design. The results showed that breeding program could rescue declining iron contents in modern wheat cultivars. In conclusion, domestication and green revolution has changed genetic makeup of wheat crop and narrowed its genetic base. However, grain quality and yield can be improved simultaneously by breeding strategies.
Keywords: Green revolution; landraces; narrow genetic base; domestication; bioavailable iron; triple test lattice